Spontaneous Rupture of Uterus in Midtrimester Pregnancy Due to Increased Uterine Pressure with Previous Laparoscopic Myomectomy - Kiseli, Mine; Artas, Hakan; Armagan, Figen; Dogan, Zeynep (Royan Inst, 2013)
Uterine rupture is a life threatening condition for both the mother and her fetus. It may be seen in the second trimester usually after induction for pregnancy termination in a scarred uterus. Spontaneous rupture in the second trimester before labor is a very rare condition. Here, we report a case of uterine rupture at 23-week pregnancy due to elevated uterine pressure with a history of laparoscopic myomectomy one year before admission. She was symptomatic for diffuse abdominal pain and the ultrasonographic image was interpreted as amniotic band. Four days later, because of deterioration of the patient and fetal bradycardia urgent laparotomy was performed. Fundal rupture with fibrotic borders suggested that a chronic event was seen. Laparoscopic myomectomy has advantages over laparatomy but the possibility of uterine rupture in following pregnancies should not be underestimated. Therefore, repair of the myometrium should be carefully assessed.
Keywords: Uterine Rupture; Uterien Myomectomies; laparoscopy; Midtrimester